Heavy oil production processes. - Speight, James G. (Elsevier Science, 2013)
As conventional-oil resources are depleted worldwide, vast heavy oil reserves available in various parts of the world become increasingly important as a secure future energy source. Brief but readable, Heavy Oil Production Processes discusses the latest improvements in production processes including; thermal methods (steam floods, cyclic steam stimulation, SAGD) as well as non-thermal methods (cold flow with sand production, cyclic solvent process, VAPEX). The book begins with an overview of the chemistry, engineering, and technology of heavy oil as they evolve into the twenty-first century.